The struggle in Black and brown : African American and Mexican American relations during the civil rights era - Behnken, Brian D. (Justice and social inquiry., 2011)
It might seem that African Americans and Mexican Americans would have common cause in matters of civil rights. This volume, which considers relations between blacks and browns during the civil rights era, carefully examines the complex and multifaceted realities that complicate such assumptions-and that revise our view of both the civil rights struggle and black-brown relations in recent history. Unique in its focus, innovative in its methods, and broad in its approach to various locales and time periods, the book provides key perspectives to understanding the development of America's ethnic a.